Optimization of hole spacing for cut-top blasting based on new hole-sealing technology - Wang, Chao; Yin, Zhiqiang; Ma, Yankun; Chen, Deren; Wang, Dengke; Zhao, Aohan (Frontiers in Earth Science, 2023)
Coal belongs to non renewable resources, and improving the economic and social benefits of enterprises is an urgent and significant issue facing coal mines. In order to reduce the construction cost of mining tunnels, a new pouch sealing technology has been developed. Through on-site experiments, the optimal sealing material ratio has been optimized, The expansion law of cracks and the cutting effect of the roof were investigated under the conditions of 0.7, 1.0, and 1.1m hole spacing and different sealing methods in the 11503W working face of Zhaizhen Coal Mine in Shandong Province. The results indicate that using the 1.5m single-pouch sealing technology in blasting experiments, a water-to-cement ratio of 1:1 for the sealing material can achieve the required sealing strength and temperature without causing punching. When the hole spacing is 1m, the blasting effect is optimal, with individual holes effectively achieving a cutting seam length of approximately 0.5m. Significant through-going cracks appeared inside the holes, with a total length of about 7m. After blasting with the new pouch sealing technology, the displacement and floor heave volume on both sides of the roadway are lower than those of the traditional yellow mud sealing method, and the floor heave volume is reduced by 37% and 53% respectively. Based on the summary of field tests and combined with the theory of shaped charge blasting, the blasting parameters can be optimized to reduce the construction cost and waste of resources.